2008
DOI: 10.1007/s11916-008-0011-8
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and chronic daily headache

Abstract: Population studies suggest that obesity is associated with migraine progression from episodic to chronic daily headaches. Although not a risk factor for episodic migraine, obesity is associated with frequent and severe headaches among migraineurs. We suggest that obesity is an exacerbating factor for migraine. This association seems to be specific to migraine and does not apply to tension-type headache. We review the clinical evidence that links obesity and migraine progression. We then review the potential pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 40 publications
(41 reference statements)
1
29
0
3
Order By: Relevance
“…64 The incidence of obesity in two pediatric headache clinic based studies, one on those with CDH, was not different from that in the general population; subjects were not stratified by gender. 20,65 Overweight females had a near four fold excess risk of headache when compared to normal-weight girls; there was no relationship between weight and headache in males.…”
Section: Obesitymentioning
confidence: 87%
“…64 The incidence of obesity in two pediatric headache clinic based studies, one on those with CDH, was not different from that in the general population; subjects were not stratified by gender. 20,65 Overweight females had a near four fold excess risk of headache when compared to normal-weight girls; there was no relationship between weight and headache in males.…”
Section: Obesitymentioning
confidence: 87%
“…It has been shown that overweight and obese migraneurs have an increased risk of having more frequent migraine attacks and chronic migraine 15 . If obesity is an exacerbating factor for migraine and if the practice of physical practices reduces the risk of obesity 16 it could be argued that physical practice reduces the impact of migraine by reducing weight.…”
Section: Discussionmentioning
confidence: 99%
“…Migraine individuals with obesity or overweight have increased risk of greater frequency of migraine attacks 15 . Weight management has been suggested to be part of migraine treatment and aerobic physical practices are one of the main strategies for weight loss and weight control 16,17 .…”
mentioning
confidence: 99%
“…Obesity is a leading risk factor for death globally [9,25] and it is projected that around 50% of adults will be obese by 2030 [26]. Worldwide, an estimated 4 billion adults are overweight or obese [25].…”
Section: Chronic Musculoskeletal Pain and Obesitymentioning
confidence: 99%
“…Evidence suggests that improvement in pain outcomes associated with weight reduction is mediated by a decrease in load on weight bearing joints [6] improvement in joint alignment [7] and improvement in posture (see [5] for review). However, individuals with headaches and chronic widespread pain experience pain in both weight bearing and non-weight bearing parts of the body and therefore it cannot be attributed to mechanical overloading [2,[8][9][10].…”
Section: Introductionmentioning
confidence: 99%